СТУДЕНТ ЖАСЛАРДЫҢ АНЫҚ МҮТӘЖЛИГИНЕ ТИЙКАРЛАНҒАН ДЕНЕ МӘДЕНИЯТЫ ҲӘМ ОНЫҢ ТҮРЛЕРИ - Турдымуратов, Ж.А.; Сейтмуратов, Т.Ш.; Тойлибаев, С.М. (FAN va JAMIYAT, 2016)
The article deals with the formation and development of skills of physical culture for humanistic full style and way of life of the youth.